Development of building comfort index and model in a tropical urban environment - Roslan, Siti Nur Aliaa (2017)
This study investigates on the internal climate modeling of buildings in an urban area situated at the Infrastructure University Kuala Lumpur (IUKL). The factors that contribute to the effect of building climate are being identified and the building climate information portrays by using the Geographical Information System (GIS). The main contributing factors of building climate are building design, building material, orientation of the building towards the sun and surrounding climate around the building. These factors contribute to the comfort condition of the rooms within the buildings. The main objective of this study is to develop a building climate modelling using a geospatial technologies which includes to investigate the building climate factors based on the building climate data collected from building samples, producing building comfort index (BCI) of each building that the building climate data and information collected based on the contributing factors and demonstrate a 3D model of building geometry from a 2D building map and building height information by using geographical information system (GIS). In order to collect the required data and information, several devices will be used. They are temperature meter, humidity meter, and noise recognizer. The building comfort data collected from each room are room temperature, room humidity and room temperature. The study area is in Kajang, Selangor area, which is being identified as an urban area. Buildings chosen are composed of ten (10) buildings in Infrastructure University Kuala Lumpur (IUKL). Data are collected from different types of rooms namely laboratories, classrooms, offices, library, and many other function of the room. Identification and discussion will be focusing on the influence of climate change towards building performance and building climate, the influences of climate change in areas that affects building performance and building climate. Building Comfort Index (BCI) is being developed based on the individual building temperature comfort index, building humidity comfort index and building noise comfort index. The results of the study revealed that the building climate index (BCI) for all buildings in IUKL comprise of six (6) buildings are having BCI of Comfortable and four (4) buildings with BCI of Less Comfortable. The building climate model (BCM) also portrayed in three dimensional in order to give better view to the end users. A mathematical equation was obtained from the data collected by using the statistical power formula and tolerances of the data were being obtained from predicted data which has 72% tolerance and onto tested data which has 93% tolerance. The results of the study implicate building manager, architect, building surveyor, town planner and building user. It is hoped that further studies focus on obtaining the BCI of the buildings once in every three months of the year.